Conservation challenges and action for the Critically Endangered Singapore freshwater crab Johora singaporensis. Issue 2 (29th April 2014) - Ng, Daniel J.J.; Yeo, Darren C.J.; Sivasothi, N.; Ng, Peter K.L.
Abstract: The Singapore freshwater crab Johora singaporensis is known only from three streams in Singapore and is among the top 100 most threatened species in the world. It is the only member of the genus Johora, endemic to the Malay Peninsula, to be categorized as Critically Endangered on the IUCN Red List. Extensive surveys conducted over 1 year to determine the extent of the species' distribution revealed that the population has declined significantly at its type locality in Bukit Timah Nature Reserve, Singapore Island's oldest protected forest area. The species remains extant in two unprotected streams in Bukit Batok and Bukit Gombak, which are located outside the nature reserve. Acidification of streams as a result of acid precipitation may be a factor in the decline of the species. If so, this will be the first documented instance of a species being affected negatively by anthropogenic acidification of a tropical freshwater system. The occurrence of this threatened species in a protected area has not, therefore, guaranteed its survival. There is a need for long-term and continuous monitoring of species of high conservation value, together with other measures that focus on habitat protection. Conservation efforts by the National Parks Board of Singapore in collaboration with other government agencies are ongoing in an effort to ensure the survival of this important species.